2009
DOI: 10.1177/1066896909331994
|View full text |Cite
|
Sign up to set email alerts
|

The Value of CD23 Expression as an Additional Marker in Distinguishing Mediastinal (Thymic) Large B-Cell Lymphoma From Hodgkin Lymphoma

Abstract: Mediastinal diffuse large B-cell lymphoma (Med-DLBCL) is a subtype of DLBCL that has morphologic and clinical similarities and phenotypic overlaps with classical Hodgkin lymphoma (CHL) involving the mediastinum. CD23 is a marker that has been previously reported in Med-DLBCI and is proposed in the differential diagnosis of M-DLBCL and CHL. A panel of immunostains, including CD45, CD20, CD3, CD30, CD15, CD21, and CD23 as well as Eber was performed on Med-DLBCL and 20CHL. 23/27 Med-DLBCL (85%) were positive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 25 publications
1
13
1
2
Order By: Relevance
“…Useful immunophenotypic markers for this purpose include CD15, a well-established marker of classical Hodgkin lymphoma that was found to be expressed in 17/20 cases (85%) of classical Hodgkin lymphoma but none of 27 cases of primary mediastinal large B cell lymphoma in a recent study by Salama et al 18 That study also found that CD23, one of the immunophenotypic markers useful for distinguishing primary mediastinal large B cell lymphoma from diffuse large B cell lymphoma, was expressed in 23/27 cases (85%) of primary mediastinal large B cell lymphoma but only 2/18 cases (11%) of classical Hodgkin lymphoma, in rare, scattered Reed-Sternberg cells. 18 MAL, another primary mediastinal large B cell lymphoma marker, was found to be expressed in only 3/31 cases of classical Hodgkin lymphoma, 10 so it too may be useful for this application. In contrast, TRAF and REL fail to distinguish primary mediastinal large B cell lymphoma from classical Hodgkin lymphoma: 21/25 cases (84%) of classical Hodgkin lymphoma were found to be immunoreactive for TRAF and 23/25 cases (92%) were immunoreactive for REL.…”
Section: Discussionmentioning
confidence: 99%
“…Useful immunophenotypic markers for this purpose include CD15, a well-established marker of classical Hodgkin lymphoma that was found to be expressed in 17/20 cases (85%) of classical Hodgkin lymphoma but none of 27 cases of primary mediastinal large B cell lymphoma in a recent study by Salama et al 18 That study also found that CD23, one of the immunophenotypic markers useful for distinguishing primary mediastinal large B cell lymphoma from diffuse large B cell lymphoma, was expressed in 23/27 cases (85%) of primary mediastinal large B cell lymphoma but only 2/18 cases (11%) of classical Hodgkin lymphoma, in rare, scattered Reed-Sternberg cells. 18 MAL, another primary mediastinal large B cell lymphoma marker, was found to be expressed in only 3/31 cases of classical Hodgkin lymphoma, 10 so it too may be useful for this application. In contrast, TRAF and REL fail to distinguish primary mediastinal large B cell lymphoma from classical Hodgkin lymphoma: 21/25 cases (84%) of classical Hodgkin lymphoma were found to be immunoreactive for TRAF and 23/25 cases (92%) were immunoreactive for REL.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The germinal center markers CD10, BCL6, and CD23 are expressed in most cases of PMBL, in keeping with its thymic B-cell origin. 6,7 Distinguishing PMBL from NSHL can sometimes be challenging for the pathologist: NSHL has a nodular pattern of growth, as well as the presence of lacunar variants of Hodgkin/Reed-Sternberg cells with a characteristic immunophenotype. In contrast to PMBL, cells are typically CD15-positive and are strongly positive for CD30.…”
Section: 2mentioning
confidence: 99%
“…Одним из рекомендуемых режимов является DA-EPOCH-R без лучевой терапии [16]. Именно такой режим химиотерапии был начат пациентке.…”
Section: Discussionunclassified
“…Именно такой режим химиотерапии был начат пациентке. Добавление ритуксимаба к основному режиму улучшает ответ, выживаемость и уменьшает риск прогрессии забо-левания [16].…”
Section: Discussionunclassified